Gender Inequity during the Ph.D. - Epstein, Nurith; Lachmann, Daniel (My University, 2018)
Female researchers remain underrepresented in higher academic ranks, even within female-dominated fields, such as the life sciences. The phenomenon is often attributed to women’s lower publication productivity. The current article explores gender differences with respect to integration into the scientific community, pursued tasks during the Ph.D. (e.g., teaching and research), and publication productivity in the life sciences. Moreover, it explores how these variables relate to the intention of pursuing an academic research career. Survey data with recent Ph.D. graduates from the life sciences in Germany (N = 736) were analyzed through descriptive and multivariate analysis. Females had fewer publications as lead author (1.4 vs. 1.9, p = 0.05). There were no differences in pursued tasks, perceived integration into the scientific community, and co-authorship. However, Ph.D. characteristics affected females and males differently. Only male Ph.D. graduates benefited from being integrated into their scientific community by an increase in lead author publications. In contrast to male Ph.D. graduates, women’s academic career intentions were significantly affected by their integration into the scientific community and co-authorship. Results suggest that women may benefit less from their integration into the scientific community and may ascribe more importance to networks for their career progress.
Females in the Life Sciences Benefit Less from Their Integration into the Scientific Community
Keywords: Karriere; Hochschule; Universität; Geschlechterdifferenz; Frauen; Frauenanteil; Frauen in Führungspositionen; 303 Gesellschaftliche Prozesse